An Analysis of Article 411 of Law No. 1 of 2023 on Unfaithfulness as a Form of Criminal Offense - Khotimah, Viviyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The increasing prevalence of unfaithfulness as a primary cause of divorce in Indonesia underscores the urgency of effective legal intervention. This study analyzes Article 411 of Law No. 1 of 2023, which explicitly criminalizes infidelity, aiming to assess its legal interpretation, application, and implications for victim protection. The analysis is grounded in Social Exchange Theory, Legal Protection Theory, and Strain Theory to explore the socio-legal dimensions of the offense. Using normative legal research with a statute approach, the study examines statutory texts, jurisprudence, and scholarly commentary. Findings reveal that Article 411 broadens criminal liability to both married and unmarried offenders, reinforcing moral and social norms. However, implementation faces socio-cultural resistance, evidentiary challenges, and low public legal literacy. The study concludes that effective enforcement requires victim-centered legal strategies, psychological support, and public legal education to ensure the law’s preventive and restorative functions.